MALAYSIAN EXPORTS TO MIDDLE EASTERN ASIAN COUNTRIES: TRENDS AND THE ROLE OF TRADE AGREEMENTS - Tajul Ariffin Masron,; Takemi Fujikawa,; Nik Hadiyan Nik Azman, (Asian Academy of Management Journal, 2014)
Malaysia’s remarkable economic performance during the past three decades is partly due to the country’s successful export sector. Nonetheless, the growth of emerging economies necessitates change in the structure of Malaysia’s export sector. With slow economic growth in its primary trading partners, there is a pressing need for Malaysia to change its current export structure, which relies heavily on western industrialised countries as export destinations. By doing so, Malaysia can diversify its economy through agreements with new export destinations with which it currently has low bilateral trade. This paper aims to examine the trends of Malaysia's exports to Middle Eastern Asian Countries (MEACs) that are similar to Malaysia in that MEACs are also Islamic countries. Proposing MEACs as Malaysia's new main export destinations, this study will examine the probable impact of various trade agreements signed between MEACs and other countries on Malaysian exports to MEACs. Applying panel data analysis, this study observes that trade agreements between MEACs and other countries do not exert negative effects on Malaysian exports to MEACs.